2013
DOI: 10.1021/om400185q
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bis(1,3,2-diazaphospholidine) Ligands for Asymmetric Catalysis

Abstract: A family of modularly designed chiral bis-1,3,2-diazaphospholidines with N-aryl substituents (NP-PN) is reported. These compounds have been prepared in two steps from readily available (R,R)-1,2-diaminocyclohexane and tetrachlorodiphosphines. Examples in the set differ in the backbone and the aryl substituents aiming at their application in asymmetric catalysis. Thus, [Rh(NBD)(NP-PN)]BF 4 complexes lead to active catalysts in the hydrogenation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In 2013, Pizzano 57 introduced chiral bis- N , N ′-diphenyl-1,3,2-diazaphospholidine (NP-PN) as a DACH ligand L7 . Upon addition to the cationic norbornadiene Rh(I) complex [Rh(NBD) 2 ]BF 4 , the active catalyst DACH [Rh(NBD)(NP-PN)]BF 4 is generated.…”
Section: Catalytic Asymmetric Hydrogenation Of Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Pizzano 57 introduced chiral bis- N , N ′-diphenyl-1,3,2-diazaphospholidine (NP-PN) as a DACH ligand L7 . Upon addition to the cationic norbornadiene Rh(I) complex [Rh(NBD) 2 ]BF 4 , the active catalyst DACH [Rh(NBD)(NP-PN)]BF 4 is generated.…”
Section: Catalytic Asymmetric Hydrogenation Of Alkenesmentioning
confidence: 99%
“…It was reported that the active catalyst completed the hydrogenation of 19 with 100% conversion at S/C = 100 at 24 h. The L7 ligand was also used for hydroformylation of vinyl acetates with excellent regioselectivity and moderate enantioselectivity (up to 65%). 57…”
Section: Catalytic Asymmetric Hydrogenation Of Alkenesmentioning
confidence: 99%
“…Consequently, the development of more efficient ligands for a range of catalytic processes is still a vital research topic. During the past decade, new families of chiral phosphines, including monodentate phosphines, bis­(aminophosphine)-type ligands, phosphino-phosphite (P-OP), phosphino-phosphoramidite, spiroketal , or supramolecular-type biphosphines, and others, , have found widespread use in the rhodium-catalyzed AH of N -acyl enamines . Among these, the past decade has witnessed the development of P -stereogenic electron-rich alkyl phosphines as highly proficient ligands. ,, Figure shows the most relevant P -stereogenic ligands used in the rhodium-catalyzed AH of benchmark enamides (Table ).…”
Section: Asymmetric Hydrogenation Of Enamidesmentioning
confidence: 99%
“…To finalize this section, we consider a unique bis(1,3,2diazaphospholidine) ligand used for the asymmetric Rh hydrogenation of a methyl acetamidoacrylate (MAA) to give N-acetylalanine (Scheme 20). 48 Unfortunately, the authors only selected one substrate for their study, i.e., MAA, but they screened four different precatalysts (Scheme 20A). All of the reactions were quantitative and in favor of the R-enantiomer.…”
Section: ■ Introductionmentioning
confidence: 99%